Pain in Children: Assessment and Nonpharmacological Management. (7th June 2010) - Srouji, Rasha; Ratnapalan, Savithiri; Schneeweiss, Suzan
Abstract : Pain perception in children is complex, and is often difficult to assess. In addition, pain management in children is not always optimized in various healthcare settings, including emergency departments. A review of pain assessment scales that can be used in children across all ages, and a discussion of the importance of pain in control and distraction techniques during painful procedures are presented. Age specific nonpharmacological interventions used to manage pain in children are most effective when adapted to the developmental level of the child. Distraction techniques are often provided by nurses, parents or child life specialists and help in pain alleviation during procedures.